Proof of the Main Actors of Narcotics Abuse in the Investigation Process - Fahri Fuad; Syamsul Haling; Muliyadi Muliyadi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
This study aims to provide knowledge to investigators to determine the main perpetrators in the criminal act of abusing narcotics illicit traffic in the investigation process. And to find out the investigator's strategy in proving the main perpetrators of narcotics crime abuse in the investigation process. The research method used is normative juridical and is carried out by descriptive analysis. Sources and types of data used are secondary data. The data collection technique uses literature study, and the data obtained will be analyzed qualitatively. The results of the research and discussion indicate that (1) In determining the qualifications of the main perpetrators of narcotics crime abuse in the investigation process, they must go through several stages, including receiving reports, conducting investigations, arrests, searches, confiscations, examination of suspects and witnesses, detention, and delegation. the case file along with the suspect to the prosecutor's office and in the investigation process must meet at least two valid pieces of evidence. (2) The investigator's strategy in proving the qualifications of the main perpetrators of narcotics crime abuse in the investigation process, namely: Investigators still refer to the basic elements of the article that are applied to the perpetrators; supervise investigators through online applications in a structured manner; improve IT-based intelligence facilities and infrastructure. and eliminate personal interests in handling the narcotics crime investigation process. The researcher's suggestions are (1) it is better if the terms of the main perpetrators of narcotics crimes are included in the law so as not to cause other interpretations of the main actors with couriers and abusers. (2) It is better for law enforcement officers to understand and realize that it is necessary to eliminate the behavior of some members of the National Police and BNN who are still deviant, tend to seek personal gain, by commercializing narcotics cases and some even being their backing, and so on.